Komunikasi Horizontal dan Kompensasi yang Dimoderasi Disiplin Kerja Karyawan terhadap Semangat Kerja Karyawan - Ardiansyah, Ahmad (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
The purpose of this study was to determine the effect of horizontal communication and compensation on employee morale at the Deli Serdang Food Security Service, both partially and simultaneously. To find out whether employee work discipline moderates the influence of horizontal communication and compensation to employee morale at the Deli Serdang Food Security Service. The population in this study was 69 people, and by using the saturation sampling technique obtained a sample of 69 people. The analysis technique used is multiple linear regression and MRA. The results showed that horizontal communication had a significant effect on the morale of the cloud service employees at the Deli Serdang Food Security Service. Compensation affects employee morale at Deli Serdang Food Security Service. The conclusion that can be obtained from the results above is that the moderator has proven significant in influencing horizontal communication on employee morale. The conclusion that can be obtained from the above results is that the moderator is proven to be significant in influencing compensation to employee morale.